2005
DOI: 10.1002/app.22698
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor permeability of poly(lactide)s: Effects of molecular characteristics and crystallinity

Abstract: Amorphous-made poly(l-lactide) [i.e., poly(l-lactic acid) (PLLA)], poly(l-lactide-co-d-lactide)-[P(LLA-DLA)](77/23), and P(LLA-DLA)(50/50) films and PLLA films with different crystallinity (X c ) values were prepared, and the effects of molecular weight, d-lactide unit content (tacticity and optical purity), and crystallinity of poly(lactide) [i.e., poly(lactic acid) (PLA)] on the water vapor permeability was investigated. The changes in number-average molecular weight (M n ) of PLLA films in the range of 9 ϫ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 29 publications
(28 reference statements)
4
89
0
Order By: Relevance
“…He reported activation energies of 5 and − 0.1 kJ/mol for amorphous and crystalline PLA, respectively [45]. In a more detailed study by Tsuji and others [46], the effects of D-lactide content, degree of crystallinity, and Mw of PLA films on WVTR were studied. They observed the WVTR of PLA films decreased monotonically with increasing crystallinity from 0% to 20%, while leveled off for crystallinity exceeding 30%; so they suggested this change due to the higher resistance of restricted amorphous regions to water vapor permeation compared with that of the free amorphous regions.…”
Section: Properties Of Lactic Acid-based Polymersmentioning
confidence: 99%
“…He reported activation energies of 5 and − 0.1 kJ/mol for amorphous and crystalline PLA, respectively [45]. In a more detailed study by Tsuji and others [46], the effects of D-lactide content, degree of crystallinity, and Mw of PLA films on WVTR were studied. They observed the WVTR of PLA films decreased monotonically with increasing crystallinity from 0% to 20%, while leveled off for crystallinity exceeding 30%; so they suggested this change due to the higher resistance of restricted amorphous regions to water vapor permeation compared with that of the free amorphous regions.…”
Section: Properties Of Lactic Acid-based Polymersmentioning
confidence: 99%
“…For PLA, it is known that the barrier properties are lower than those of PHBV. 1,9,10 Tsuji and Tsuruno 11 stated WVTR of PLA films with a thickness of 25 µm of 98 -224 g m -2 d -1 depending on their ratio of stereocomplexes.…”
Section: Blending Of Polyhydroxybutyrate-co-valerate With Polylactic mentioning
confidence: 99%
“…Work by Tsuji et al 13 has investigated the effect of crystallinity on water permeability of PLA and found a monotonic decrease with increasing crystallinity from 0% to 20%, which then levelled off. In a recent publication, Tsuji and Tsuruno 14 reported further studies of water vapour permeability of poly(L-lactic acid)/poly(D-lactic acid) blend films in which crystallinity ranged from 0% to 30%.…”
Section: Water Vapour Permeability Measurementsmentioning
confidence: 99%
“…The effects of molecular characteristics and crystallinity on the water vapour permeability of poly(lactides) has been researched by Tsuji et al 13,14 It was reported that WVTR decreased monotonically with increasing crystallinity up to 20% and levelled off at 30% due to the higher resistance of "restricted" amorphous regions. Another study by Cocca et al 15 has reported water vapour permeability of poly(l-lactide) with crystallinity varying between 33% and 45%.…”
Section: Introductionmentioning
confidence: 99%